The effect of FinTech development on financial stability in an emerging market: The role of market discipline - Quang Khai Nguyen; Dang Van Cuong (Research in Globalization, 2022)
This study investigated the impact of financial technology (FinTech) development on financial stability in an emerging market. By using data from 37 commercial banks in Vietnam for the period 2010-2020, the study found that FinTech development negatively affected financial stability, and market discipline can mitigate this effect. However, heterogeneity analysis further showed that the negative effect of FinTech development on financial stability is stronger when the degree of financial stability is low, and the role of market discipline also becomes more important in such a situation. As another extension, we also found that the negative impact of FinTech on financial stability and the role of market discipline in mitigating such effect becomes stronger when banks have higher state ownership and becomes weaker when banks have higher foreign ownership. Our study provides important implications for regulators to develop FinTech and maintain financial stability in emerging markets.
Keywords: 330; Emerging market; Financial stability; FinTech development; Market discipline